The vaginal microbiome of sub-Saharan African women: revealing important gaps in the era of next-generation sequencing - Odogwu, Nkechi Martina; Olayemi, Oladapo O.; Omigbodun, Akinyinka O. (PeerJ, 2020)
Accurate characterization of the vaginal microbiome remains a fundamental goal of the Human Microbiome project (HMP). For over a decade, this goal has been made possible deploying high-throughput next generation sequencing technologies (NGS), which indeed has revolutionized medical research and enabled large-scale genomic studies. The 16S rRNA marker-gene survey is the most commonly explored approach for vaginal microbial community studies. With this approach, prior studies have elucidated substantial variations in the vaginal microbiome of women from different ethnicities. This review provides a comprehensive account of studies that have deployed this approach to describe the vaginal microbiota of African women in health and disease. On the basis of published data, the few studies reported from the African population are mainly in non-pregnant post pubertal women and calls for more detailed studies in pregnant and postnatal cohorts. We provide insight on the use of more sophisticated cutting-edge technologies in characterizing the vaginal microbiome. These technologies offer high-resolution detection of vaginal microbiome variations and community functional capabilities, which can shed light into several discrepancies observed in the vaginal microbiota of African women in an African population versus women of African descent in the diaspora.
Keywords: Vaginal microbiome; Sub-Saharan African women; High throughput sequencing; Next generation sequencing